Growth and maturation of adolescent female gymnasts, swimmers, and tennis players - Erlandson, M. C.; Sherar, L. B.; Mirwald, R. L.; Maffulli, N.; Baxter-Jones, A. D. (Medicine & Science in Sports & Exercise, 2008)
Intensive training at a young age may adversely affect the growth and sexual maturation of female athletes, resulting in compromised adult stature.